The role of geographic spillovers in employment policy planning: an empirical investigation for Russian regions. Issue 3 (11th June 2018) - Aldieri, Luigi; Kotsemir, Maxim; Vinci, Concetto Paolo
Abstract : Purpose: The purpose of this paper is to look at the factors driving labour creation in Russia, while paying attention to the role of innovation policy. The study considers innovation variables with indicators linked to social conditions (social filter component) and geographical spillovers for 85 regions during the period 2010-2016. Design/methodology/approach: In particular, the study uses latitude and longitude coordinates to compute the distance between Russian regions according to the Haversine formula. In this manner, it measures the spillovers as the weighted sum of R&D capital stock on the basis of computed distance, according to the accessibility index procedure. Findings: The finding is very important in terms of policy implications for supporting employment. As the results stress that own innovation produces labour creation effects, while knowledge spillovers are labour-saving, the study could conclude that regional innovation policy may have undetermined the objective of an efficient level of absorptive capacity able to benefit positively from external innovation. Originality/value: The study contributes to the literature by exploring whether geographical spillovers are labour-friendly or labour-saving in Russia.